2006
DOI: 10.1021/bm060397k
|View full text |Cite
|
Sign up to set email alerts
|

Quantal Self-Assembly of Polymer Layers in Polypeptide Multilayer Nanofilms

Abstract: Simple molecular models predict key aspects of the "microscopic" assembly behavior of various peptide systems in the fabrication of multilayer films. Such films show substantial differences in density for different peptide systems. The data suggest that exponential film growth is possible in the absence of polymer diffusion and that "macroscopic" assembly behavior is more a function of peptide-peptide interactions than peptide sequence alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Optical thickness of the films followed the trend: pH 7.4 b pH 5.5 b pH 4.0 ( Figure 2, A), consistent with previous findings [24]. Film thickness was least when the linear charge density of peptides was greatest [6,24]. The electrostatic force repels peptides of the same sign of charge, limiting the amount of polymer deposited per layer [25].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Optical thickness of the films followed the trend: pH 7.4 b pH 5.5 b pH 4.0 ( Figure 2, A), consistent with previous findings [24]. Film thickness was least when the linear charge density of peptides was greatest [6,24]. The electrostatic force repels peptides of the same sign of charge, limiting the amount of polymer deposited per layer [25].…”
Section: Resultssupporting
confidence: 87%
“…The main driving force for the adsorption of species from solution is electrostatic attraction and the entropy gain from release of counterions; the availability of charged groups on the film surface is crucial for controlled deposition of material. Hydrogen bonds and hydrophobic interactions too can influence LBL multilayer nanofilm assembly [4][5][6]. Polymers in adjacent layers interpenetrate [7,8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we have demonstrated that control over peptide sequence represents a means of control over useful film properties. [42][43][44] Assembly behavior of given polypeptides in a multilayer film will depend on propensity to form secondary structure, pH, ionic strength, presence of cosolvents, and so on. The broad range of process control variables enables the engineering of physical, chemical, and biological properties of multilayer filmbased structures.…”
Section: Discussionmentioning
confidence: 99%